Evaluating Antibacterial And Anti-Biofilm Properties Of Copper And Zinc In Beta Tricalcium Phosphate Against Staphylococcus Epidermidis - Aristo, Emanuel Jovan; Situmorang, Evi Margareta; Octavia, Mora; Edbert, Daniel (Poltekkes Kemenkes Semarang, 2024)
Staphylococcus epidermidis is a common pathogen responsible for peri-implantitis, an infection localized around dental implants. Its virulence is largely attributed to biofilm formation, which enhances resistance to antibiotics and immune defenses. The challenge of treating S. epidermidis is further compounded by its resistance to several antibiotics, including methicillin. This study aimed to evaluate the antibacterial and anti-biofilm properties of a copper-zinc (Cu-Zn) metal alloy and its efficacy when integrated with beta-tricalcium phosphate (β-TCP) as a graft medium against S. epidermidis using in vitro methods. This research employs Staphylococcus epidermidis ATCC 12228. Antibacterial activity was assessed using Direct contact test and viability count via Colony-Forming Unit (CFU) analysis, while biofilm formation was evaluated using the tube adherence method. Increasing copper and zinc concentrations enhanced antibacterial efficacy, with Cu-Zn-β-TCP suspensions showing significantly greater antibacterial activity (p = 0.01) and improved anti-biofilm properties compared to Cu-Zn suspensions without β-TCP. The incorporation of copper and zinc effectively inhibited bacterial growth and biofilm formation of S. epidermidis. Furthermore, the Cu-Zn alloy demonstrated higher efficacy when used in conjunction with β-TCP as a graft medium, suggesting its potential for managing peri-implantitis.